The Effect of Socratic Circles Strategy on Students’ Reading Comprehension at Eleventh Grade of SMKI Al Khoirat Kabupaten Tangerang in Academic Year 2020/2021 - Wulansari, Deis; Nuraini, Hery (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2021)
ABSTRACT The purpose of this study was determine whether there was a significant influence using Socratic Circles Strategy on Students’ Reading Comprehension at Eleventh Grade of SMKI AL KHOIRAT Kabupaten Tangerang in academic year 2020/2021. The method of the research used quantitative research with quasi-experimental research. In this research design consists of experimental class without random selection. The students was tested by using pre-test and post-test. And the result of this research was statistical calculation by kolmogorov-smirnova test, based on testing of hypothesis, it was known that the sig (0.000) was similar than 0.05. There for it can be conclude that there is a positive effect of Socratic Circles Strategy on Students’ Reading Comprehension at Eleventh Grade of SMKI AL KHOIRAT KabupatenTangerang.